An Analysis of Factors Affecting the Results of the Vietnam Bank for Social Policies (VBSP) Microcredit Use by Poor Households: A Case of Soc Son District - Nguyễn, Hải Long (2020)
Poverty has always been an obstacle for countries to achieve sustainable development goals. Microcredit has been recognized as one of the most effective tools to alleviate poverty. However, after the initial success, the effectiveness of microcredit now are widely debated. Many studies have shown that the use of such loan has some issues. For instance, the use of microfinance loan normally lies in small-scale agricultural production, which is risky and unsecured. In other words, the use of the loan may not create sustainable result and may be affected by many factors, both internal and external. This study investigates the factors that affected the usage of the microcredit loan and the result of this study may detect the important factors that can be improved to alleviate poverty. The study will use a quantitative approach with the analysis conducted with SPSS and the data collected from Soc Son District and VBSP Soc Son. On the other hand, the author also used in-depth interview with both the bank’s officers and poor borrowers in order take a closer look on the matter. To conclude, the author will suggest some recommendations for VBSP and local government to improve the usage of the loan.